Oxytocin signaling in the early life of mammals: link to neurodevelopmental disorders associated with ASD - Muscatelli, Françoise; Grinevich, Valéry (Behavioral pharmacology of neuropeptides: Oxytocin, 2018)
Oxytocin plays a role in various functions including endocrine and immune functions but also parent-infant bonding and social interactions. It might be considered as a main neuropeptide involved in mediating the regulation of adaptive interactions between an individual and his/her environment. Recently, a critical role of oxytocin in early life has been revealed in sensory processing and multi-modal integration that are essential for normal postnatal neurodevelopment. An early alteration in the oxytocin-system may disturb its maturation and may have short-term and long-term pathological consequences such as autism spectrum disorders. Here, we will synthesize the existing literature on the development of the oxytocin system and its role in the early postnatal life of mammals (from birth to weaning) in a normal or pathological context. Oxytocin is required in critical windows of time that play a pivotal role and that should be considered for therapeutical interventions.
Gesehen am 29.10.2018
First online: 16 August 2017